Identity formations as mathematical learners in the context of transition - Svensson Källberg, Petra (NOMAD Nordic Studies in Mathematics Education, 2018)
This paper explores the relation between discourses and identity formations as mathematical learners in a context of transition. The data consists of an interview with two 16 year-old immigrant girls, who were relocated when their school, in a multicultural and socio-economically disadvantaged area in Sweden, was closed. The girls showed dynamic and unstable identities by drawing on different discourses. Social relational discourses, more than mathematical pedagogical discourses, governed their actions as learners of mathematics; enabling identities as noisy, un-engaged, but able students in the old school, and as engaged and accepted, but also as strangers, in the new school.